Educational Possibilities of Keeping Goats in Elementary Schools in Japan - Koda, Naoko; Kutsumi, Shiho; Hirose, Toshiya; Watanabe, Gen (Frontiers in Veterinary Science, 2016)
Many Japanese elementary schools keep small animals for educational purposes, and the effects and challenges have been investigated. Although goats are medium-sized animals that are familiar to Japanese, few practical studies have been conducted on keeping goats in schools. This study investigated the effects and challenges of keeping goats in elementary schools and discussed its educational possibilities. A semi-structured interview survey was conducted with 11 personnel that were responsible for keeping goats in six elementary schools in urban areas. They described benefits, problems, and tips related to keeping goats. Participant observation was also conducted on daily human-goat interactions in these schools. The results indicated that children in all six grades were able to care for goats. Goats were used for various school subjects and activities. As a result of keeping goats, children developed affection for them, attitude of respect for living things, greater sense of responsibility, and enhanced interpersonal interactional skills. Stronger ties between the schools and parents and community were developed through cooperation in goat-keeping. Some anxieties existed about the risk of injury to children when interacting with goats. Other challenges included the burden of taking care of the goats on holidays and insufficient knowledge about treatment in case of their illness or injury. The results suggested similarities to the benefits and challenges associated with keeping small animals in elementary schools, although the responsibility and the burden on the schools were greater for keeping goats than small animals because of their larger size and the need for children to consider the goats’ inner state and to cooperate with others when providing care. At the same time, goats greatly stimulated interest, cooperation, and empathy in children. Goats can expand educational opportunities and bring about many positive effects on child development.